1993
DOI: 10.1590/s0036-46651993000200009
|View full text |Cite
|
Sign up to set email alerts
|

Simplified fluorescent inhibition microtest for the titration of rabies neutralizing antibodies

Abstract: A simplified fluorescence inhibition microtest (SFIMT) was standardized for the evaluation of antirabies serum neutralizing antibodies based on the rapid fluorescent focus inhibition test (RFFIT) and the fluorescence inhibition microtest (FIMT). The simplified test showed reproductibility similar to that of the FIMT with advantages as easier executation and quicker reading. A simple pre-treatment of Brazilian microplates produced for immune enzymatic assays (PROSIL) gave equivalent results and substantial coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 4 publications
1
13
0
5
Order By: Relevance
“…The value of correlation coefficient reported here shows that there was a good relation between results obtained with MNT and IPVN for dogs and cattle, r = 0.9949 and 0.9307, respectively (Figure). These results were similar and higher to those reported before (Favoretto et al 1993, Gamoh et al 1996, Sugiyama et al 1997, Briggs et al 1998, Cleaveland et al 1999, Katayama et al 1999, Cliquet et al 2000 when the ELISA and RFFIT methods were used for the same purpose.…”
supporting
confidence: 89%
“…The value of correlation coefficient reported here shows that there was a good relation between results obtained with MNT and IPVN for dogs and cattle, r = 0.9949 and 0.9307, respectively (Figure). These results were similar and higher to those reported before (Favoretto et al 1993, Gamoh et al 1996, Sugiyama et al 1997, Briggs et al 1998, Cleaveland et al 1999, Katayama et al 1999, Cliquet et al 2000 when the ELISA and RFFIT methods were used for the same purpose.…”
supporting
confidence: 89%
“…As amostras de soro foram centrifugadas a 1000xg por 15 minutos, e o soro congelado a -20°C. O título de anticorpos neutralizantes foi avaliado por meio do microteste de inibição de fluorescência simplificado (SFIMT) (Favoretto et al, 1993).…”
Section: Methodsunclassified
“…Since cell-culture vaccine (CCV) for human treatment is not available in the Brazilian Public Health Services, we have studied different immunization schedules employing brain tissue vaccines (2,3). In a field study carried out in 29 different localities in the State of São Paulo, we found that the preexposure anti-rabies immunization regimen currently used in Brazil (a 1-ml im dose of suckling mouse brain vaccine (SMBV) on days 0, 2, 4 and 28) showed an elevated rate of unsatisfactory results, i.e., virus-neutral-C.R.…”
mentioning
confidence: 99%
“…Virus-neutralizing antibodies against both the PV and CVS strains were submitted to the simplified fluorescence inhibition microtest as previously described (2). VNA is expressed as IU/ml, using as reference an equine hyperimmune serum adjusted to a concentration of 2.0 IU/ml.…”
mentioning
confidence: 99%